Kewenangan Menangkap Dan Mengadili Bajak Laut Di Wilayah Yurisdiksi Indonesia Berdasarkan Hukum Internasional - Dzaky Hanif; Adrian Saputra; Rangga Abrari Kahfi; Yuda Pangestu; Dewi Rahmawati Gustini (Peneliti.net, 2023)
In terms of international law, piracy is regarded as a criminal conduct that threatens trade and international security. According to the 1982 United Nations Convention on the Law of the Sea, any State is allowed to seize a ship that is being used by pirates or that has been captured by them and is in its possession, as well as to arrest people and seize any property that may be on board. The UNCLOS III agreement on the high seas, namely paragraphs 100–107 of the agreement, regulates pirates or sea pirates.Whereas in its application, it calls for National Laws from each nation to control specific issues in putting the convention's principles into practice. In accordance with international law, each state is legally obligated to fully cooperate with one another in the fight against piracy on the loose ocean and in other areas that are beyond its territorial control. The criminal code (